Rotator cuff tendons of the shoulder joint : anatomy and investigation of strain profile - Sheng, Jia-Min (2013)
The prevalence of rotator cuff tears found in elderly patients in Singapore has led to an appreciation of the importance of studying its causes and appropriate treatment. The objective of this project is to investigate the effect of arm positions, tendon tears and surgical repair on the strain profile of the rotator cuff tendons. Nine fresh-frozen shoulders were tested using displacement variable reluctance transducers (DVRTs) to measure the strains of the supraspinatus, infraspinatus and subscapularis tendons simultaneously with the glenohumeral joint intact at various arm positions. This was followed by simulated tears and surgical repairs. The rotator cuff strains showed varying trends at different arm positions. The strain difference between the articular and bursal side of the supraspinatus implied the occurrence of shearing which may cause intratendinous tears. A full thickness tear at the anterior supraspinatus increased the strain at the posterior supraspinatus. Single-row repairs increased the strain difference between the articular and bursal surfaces of the tendon. It was shown that double-row repairs restored the strains to the intact strain condition and thus may be more efficient for tendon healing than single-row repairs. Elevation of arm at higher angles should be avoided after surgical repairs due to the high differential strains between the two surfaces of the supraspinatus. The footprint areas and dimensions of the rotator cuff tendons from nineteen Asian shoulder specimens were collected. The knowledge of the average footprint area of each tendon helps the surgeon to restore torn tendons to their functional anatomic positions. Tensile tests were conducted to obtain the elastic modulus of the tendons. The strain, anatomical data and tensile properties collected were used in the validation of a three-dimensional finite element model that was developed. The FE model showed similar trends in the strain as compared to the experimental results. High shear stresses were observed near the footprint within the supraspinatus. These stresses could initiate tears, propagate intratendinous defects and ultimately cause delamination of the tendon. From the FE model developed, it was observed that the strain varies linearly across the supraspinatus between the articular and bursal surface at elevated angles. It is hoped that the results obtained from this study can be useful for the surgical treatment and rehabilitation of patients with rotator cuff tears.